Role of dehydroepiandrosterone and cortisol in nociceptive sensitivity to thermal pain in anorexia nervosa and healthy women - Yamamotova, Anna; Kmoch, Vladimir; Papezova, Hana (Neuro endocrinology letters, 2012)
OBJECTIVES: Anorexia nervosa (AN) patients represent a natural model of relationship between changed hormonal level and pain perception due to lower level of sex hormones and consistently described increased pain threshold. As the adrenal stress steroid hormones (cortisol and DHEA) are known to be also changed in AN (and share a common precursor), our study was aimed to analyze the association between these hormones and pain perception in AN patients and control healthy women. METHODS: The pain threshold latencies to radiant heat stimuli were measured in 20 DSM-IV diagnosed patients with AN and in 21 healthy women. Blood samples were collected in the morning hours and analyses of the plasma levels of dehydroepiandrosterone (DHEA), its conjugated sulfate ester (DHEA-S) and cortisol were implemented. RESULTS: Thermal pain threshold was higher in AN than in healthy women and correlated negatively with the level of DHEA and positively with cortisol/DHEA(S) ratio. No significant correlation between thermal pain and hormones was found in healthy women. If both groups were pooled together, the rest pain threshold correlated negatively with DHEA-S (r=-0.42, p=0.008). CONCLUSION: We showed for the first time that sensitivity to thermal pain in women is dependent on DHEA-S and on cortisol/DHEA(S) ratio in patients with AN.
Keywords: dospělí; Matched-Pair Analysis; Female; Pain Threshold; vysoká teplota; Adult; ženské pohlaví; mladý dospělý; analýza párové shody; hydrokortison; Hot Temperature; lidé; Hydrocortisone; studie případů a kontrol; mentální anorexie; referenční hodnoty; dehydroepiandrosteron; Dehydroepiandrosterone Sulfate; Nociception; neparametrická statistika; Dehydroepiandrosterone; Case-Control Studies; Reference Values; Young Adult; Anorexia Nervosa; nocicepce; Statistics, Nonparametric; práh bolesti; dehydroepiandrosteronsulfát; Humans